Gamification: From Motivation and Challenges to Improving Academic Performance in Learning Mathematics - Núñez-Naranjo, Aracelly (2024)
Gamification is a didactic strategy that motivates and improves teaching processes, for this reason the present study has been proposed in which a methodological proposal is structured that seeks to improve academic performance using gamification as a strategy for teaching operations with applied polynomials. Students of the first year of high school of an educational institution in the city of Quito, the methodology is addressed from a descriptive and correlational level given the exploratory approach that has been carried out, for the development of the proposal the principles of gamification that relate to motivation with learning challenges, we worked with 28 students in scheduled class meetings, a pre-test and a post-test were applied to them, obtaining the following average course results: initial pre-test evaluation 4.93 and post-test -test, a value of 8.61 was obtained, evidencing an increase in the total average, with these data it is concluded that the gamification of activities and assessments if it improves the academic performance of students. © The Author(s), under exclusive license to Springer Nature Switzerland